The ecology and antimicrobial resistance of Staphylococci colonising neonates. Issue 5 (27th May 2022) - Felgate, Heather; Sethi, Dheeraj; Langridge, Gemma; Crossman, Lisa; Wain, John; Clarke, Paul; Page, Andrew; Webber, Mark A
Abstract : Coagulase Negative Staphylococci (CoNS) are common commensals of human skin, account for nearly 20% of the microbiota in infants and are thought to promote early immune responses in healthy babies. However, CoNS are opportunistic pathogens and in the UK between 2005 and 2014 were responsible for 57% of episodes of Late Onset Sepsis (LOS). In neonatal intensive care units (NICUs) this is a major concern and antiseptics are used to prevent vascular catheter infections. Chlorhexidine (CHX) and Octenidine (OCT) are the most common agents used for skin antisepsis, but evidence is emerging of antiseptic tolerance amongst CoNS. We undertook a longitudinal survey of CoNS from skin and rectal swabs isolated from babies in two NICUs from countries with different antiseptic regimens (UK and Germany). Over 1000 isolates were characterised for antimicrobial susceptibility and sequenced. The most frequent species isolated were S. epidermidis and S. haemolyticus with similar strain types present in both units. Reduced susceptibility to CHX and OCT was observed in UK isolates (where CHX is used), compared to German isolates (where OCT is used). Analysis of genome data using GWAS and clustering techniques has identified loci associated with antimicrobial susceptibility. Comparison of isolates taken on admission and thereafter, demonstrated that babies acquired isolates with decreased antiseptic tolerance after admission. This data provides new information about the phylogeny of CoNS in NICUs and suggest different potentials for selection of resistance between antiseptics commonly used in neonatal care.